Complex Protein Astrogliopathy in an Octogenarian. (July 2021) - Kovacs, G.G.; Klotz, S.; Fischer, P.; Hinterberger, M.; Ricken, G.; Hönigschnabl, S.; Gelpi, E.
Abstract : Combination of multiple neurodegenerative proteinopathies is frequent in the elderly. We report the case of an octogenarian who attempted suicide and deceased after hospital admission. Anatomical mapping was performed in several cortical and subcortical brain regions using antibodies against phospho-tau, 4R tau, 3R tau, phospho-TDP-43, ubiquitin, α-synuclein, Aβ and p62. Unexpectedly, histopathologic examination showed prominent subpial, subependymal, grey and white matter, and perivascular aging-related tau astrogliopathy (ARTAG) affecting cortical and subcortical brain regions. This pathology was associated with intermediate Alzheimer's disease neuropathologic change, cerebral amyloid angiopathy, Lewy-body-type and astroglial synuclein proteinopathy and a multiple system TDP-43 proteinopathy involving also the astroglia. This unusual case of extensive and widespread ARTAG with a complex multiproteinopathy may represent an independent disease entity in the elderly with tau astrogliopathy as the leading force. Learning Objective: Recognize astroglial protein deposits in neurodegeneration